Using acoustics to study biological activity in the Perth Canyon, Western Australia - Hawkins, Lauren; McCauley, Robert; Parnum, Iain; Saunders, Ben (2016)
The Perth Canyon, off the coast of Western Australia, is a hotspot for biological activity, high biomass and biodiversity. It is also an area that is still relatively understudied. In this study, combinations of passive and active acoustical methodologies were used to study biological activity in the Canyon; and in particular, diel vertical migration. Data from sea noise loggers and Acoustical Doppler Current Profilers (ADCPs) mounted along the Perth Canyon were collected as part of the Integrated Marine Observing System (IMOS) program. The sea noise data recorded post-sunset fish choruses and the backscatter logged by the ADCP deployments measured increased scattering in the upper layers of the waters between sunset and sunrise. These two types of data provide an insight into secondary productivity in the Perth Canyon. This study revealed a correlation between the fish chorus noise level and the increase in scattering in the water column. Future research is planned to determine the sources and the reason(s) for the temporal variation of these phenomena.